PRINSIP-PRINSIP KEPEMILIKAN SAHAM PEMERINTAH DALAM PERUSAHAAN MILIK NEGARA (STUDI PERBANDINGAN ANTARA INDONESIA DENGAN SINGAPURA) - Ni Wayan Desi Aryanti (University of Udayana, 2014)
This journal entitled “Comparative Study Concerning The Principles of Government’s Shares in State Owned Enterprise”. Problems being research in this thesis are, first: the legal standing of the state’s equity in Persero according to Indonesian corporate law and its comparison to Singapore corporate law. The second problem, what are legal implications of the government’s shares in Persero. The method being used is normative legal research through legislation and regulation approach and comparative approach. Legal materials used are primary legal materials, legal materials and secondary and tertiary legal materials, the analysis done by descriptive, evaluative, interpretative, analytical and argumentative. This research shows that according to Indonesian corporate law, the state’s equity being placed in Persero belongs to Persero and according to Singapore Law, the government’s equity being placed in Persero as the Government Linked Company belongs to the said company. Legal consequences of the government equity in Persero are: the management of the said equity is no longer subject to state budget’s principals but to good corporate government principals; contracts made by Persero binds Persero and not the government, hence compliance and liability arising from the said contracts are Persero’s liability only and therefore Persero’s claim arising from contracts belong to the said Persero. However, in practical level, there are still some inconsistency in Persero’s equity treatment (i.e. financial audit and Persero’s inability to act as the guarantor to another company). On the other side, the Government of Singapore’s equity in Temasek is managed by corporate mechanism and almost without government intervention (except for past reserves). Therefore Temasek is free to make any contract with third parties and can act as the guarantor for its subsidiary.